Pengaruh Model Pembelajaran Collaborative Learning terhadap Motivasi Belajar PAK Siswa Kelas VII SMP Negeri 1 Sipoholon Tahun Pembelajaran 2023/2024 - Asrita Anggina Sinaga; Frainskoy Rio Naibaho; Rawatri Sitanggang; Senida Harefa; Maria Widiastuti (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The aim of this research is to determine the differences in student learning motivation in PAK learning before and after it is taught using the Collaborative Learning learning model for class VII students at SMP Negeri 1 Sipoholon for the 2023/2024 academic year. The research hypothesis is: "There is a difference in students' learning motivation in PAK learning before and after learning with the Collaborative Learning learning model for Class VII Students of SMP Negeri 1 Sipoholon for the 2023/2024 Learning Year." The population is all class VII students of SMP Negeri 1 Sipoholon, totaling 163 people. The research sample was determined using the Purposive Sampling technique, namely 32 students in class VII-3 as the experimental class which used a collaborative learning model and 32 students in class VII-4 as the control class which used normal treatment (conventional class). This research method is the Quasi Experimental Design method using a Nonequivalent Control Group Design. The instrument used in this research was a 22 item questionnaire. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 0.7283 in the high category. And the average value for the control class is 0.1548, which is in the low category. Then carrying out an independent test using the t test obtained a value of t = 11.648 > t table (α = 0.05; df = 62) = 2,000. Based on the research results, it is stated that Ha is accepted and H0 is rejected. Thus, it can be concluded that there are differences in students' learning motivation in PAK learning before and after being taught using the Collaborative Learning learning model.